Three-dimensional computer-aided analysis of 293 isolated blowout fractures - which radiological findings guide treatment decision? - Pyötsiä, Krista; Lehtinen, Valtteri; Toivari, Miika; Puolakkainen, Tero; Wilson, Michael; Snäll, Johanna (Journal of oral and maxillofacial surgery, 2021)
Purpose - Our study purpose was to clarify the extent of isolated unilateral orbital blowout fracture in relation to surgical treatment and other factors behind the treatment decision. The specific aim was to determine which computer-aided measurements based on radiological images associate with treatment choice. - Methods - A retrospective cohort study was implemented on patients with an isolated unilateral orbital blowout fracture. Computer-aided measurement of fracture extent was performed. The study variables included treatment as primary outcome (surgical vs nonsurgical), post-traumatic orbital volume difference (mL) compared to contralateral orbit, fracture area (mm2), fracture depth (mm) as predictor variables, and age, sex, injury mechanism, side and site of orbital fracture and positions of recti muscles as explanatory variables. Postoperative outcomes were reported. Logistic regression analysis was used to determine the risk factors for surgery. The statistical significance level was set at P < .05. - Results - Of 293 patients, 28.0% received surgical and 72.0% nonsurgical treatment. Volume difference, fracture area and fracture depth predicted surgical outcome (P < .001). In adjusted univariate regression analyses, fractures with moderate and severe displacement of recti muscles were more likely to receive surgical treatment than fractures with mild or no displacement (OR 6.15 and 30.75, respectively, P < .001). Isolated medial wall fractures were significantly less often (OR 0.05, P = .006) and patients with older age (OR 0.97, P = .013) slightly less often treated with surgery. Patients with preoperative symptoms had more often persisting postoperative symptoms than patients without preoperative symptoms. - Conclusions - Positions of the recti muscles are an independent radiological factor guiding orbital blowout fracture treatment decision. The bony fracture extent is a combination of volume difference, fracture area and fracture depth which are strongly correlated to each other. A computer-aided method significantly facilitates the systematic evaluation of bone fragments, and the extent of orbital fractures.
Gesehen am 24.05.2022